2004
DOI: 10.1001/archpsyc.61.9.866
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Enhancement Therapy for Schizophrenia

Abstract: Background: Deficits in social cognition and neurocognition are believed to underlie schizophrenia disability. Attempts at rehabilitation have had circumscribed effects on cognition, without concurrent improvement in broad aspects of behavior and adjustment.Objective: To determine the differential effects of cognitive enhancement therapy (a recovery-phase intervention) on cognition and behavior compared with stateof-the-art enriched supportive therapy.Design: A 2-year, randomized controlled trial with neuropsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
159
1
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 495 publications
(177 citation statements)
references
References 78 publications
7
159
1
8
Order By: Relevance
“…When these cognitive changes reached a certain threshold, a reduction in social problems was also apparent. Furthermore, other randomized, controlled trials with CRT have shown various improvements in functioning ranging from improvements in obtaining and keeping competitive jobs (McGurk et al, 2005;Vauth et al, 2005), to the quality of, and satisfaction with, interpersonal relationships (Hogarty et al, 2004;Penadés et al, 2006) and the ability to solve interpersonal problems (Spaulding et al, 1999). These findings reinforce the assumption that neurocognition and functioning are strongly related and that CRT is useful in improving functioning.…”
Section: Improving Outcomes and Promoting Recovery With Crtsupporting
confidence: 57%
See 1 more Smart Citation
“…When these cognitive changes reached a certain threshold, a reduction in social problems was also apparent. Furthermore, other randomized, controlled trials with CRT have shown various improvements in functioning ranging from improvements in obtaining and keeping competitive jobs (McGurk et al, 2005;Vauth et al, 2005), to the quality of, and satisfaction with, interpersonal relationships (Hogarty et al, 2004;Penadés et al, 2006) and the ability to solve interpersonal problems (Spaulding et al, 1999). These findings reinforce the assumption that neurocognition and functioning are strongly related and that CRT is useful in improving functioning.…”
Section: Improving Outcomes and Promoting Recovery With Crtsupporting
confidence: 57%
“…Participants are asked to interpret the intentions of various actors in a scene and to produce a written report highlighting the most relevant leading roles. This program was tested in a methodologically rigorous study, with a 2 year follow-up, and showed improvements in verbal memory, processing speed, social cognition and social adjustment (Hogarty et al 2004). …”
Section: Cognitive Enhancement Therapy (Cet)mentioning
confidence: 99%
“…In order to avoid excessive univariate inference testing that could inflate experiment-wise error rates, internally consistent multivariate composite indexes of these domains were computed. Individual measures were selected for these composites based on previous literature identifying the important domains of cognitive impairment in schizophrenia (23), field standards for adjustment and symptom assessment (24, 25), as well as previous CET studies (19, 20). Measures showing poor reliability (interitem r ≤ .10) were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…In a two-year randomized-controlled trial with 121 outpatients with schizophrenia who had been ill for an average of 15.70±9.30 years, patients receiving CET demonstrated large and highly significant improvements in neurocognitive and social-cognitive function, as well as social adjustment (19). Further, these robust effects remained one year after treatment ended (20).…”
mentioning
confidence: 99%
“…CR can be characterized as provid-ing repetitive practice along with compensatory cognitive-skill acquisition focused on elementary cognitive and more complex social-cognitive measures (Heydebrand, 2007;Kurtz & Nichols, 2007;Spaulding & Poland, 2001). Research reviews and metaanalyses of randomized controlled studies indicate that CR therapy is associated with significant improvements on measures of working memory, executive function and facial affect perception, and has small effects on some symptoms (Hogarty, Flesher, Ulrich, Carter, & Greenwald, 2004;Kurtz & Nichols, 2007;McGurk, Twamley, Sitzer, McHugo, & Mueser, 2007). Evidence also indicates that when combined with vocational rehabilitation and SE services, CR produces more superior outcomes than when these interventions are provided singly in the absence of CR (Greig, Zito, Wexler, Fiszdon, & Bell, 2007;Heydebrand, 2007;Kurtz & Nichols, 2007;McGurk, Mueser, Feldman, Wolfe, & Pascaris, 2007).…”
Section: Cognitive Rehabilitationmentioning
confidence: 99%